Contribution of coiled-coil assembly to Ca2+/ calmodulin-dependent inactivation of TRPC6 channel and its impacts on FSGS-associated phenotypes - Wong, Chee Fah (Tanjong Malim, 2019)
Contribution of coiled-coil assembly to Ca2+/ calmodulin-dependent inactivation of TRPC6 channel and its impacts on FSGS-associated phenotypes by Wong, Chee Fah